The Impact of Pastoral Nurture on Member Retention in Selected Fields within the Haitian Union of the Seventh-Day Adventist Church - Pierre Caporal; Balvin B. Braham (International Journal of Engineering and Management Research, 2022)
This descriptive-correlational study sought to investigate the relationship between pastoral nurture initiatives and member retention to confirm, refute or extend pastoral nurture initiatives as effective constructs for retaining members in the church within the Northwest and South Haitian Mission of Seventh-day Adventists. Three self-reported questionnaires were used to collect data from one hundred and thirty-two (132) participants comprising the sampled population from 45 congregations in the Northwest and the South Haitian Missions. The data were coded and analysed using SPSS version 25.0 to compute mean, standard, Cronbach’s Alphas, factor analysis, Pearson Correlation, t-test and One-Way. It was found that there was no significant statistical association between membership retention and the nurturing initiative employed by the church (χ2 (df=1) = 0.015, P = 0.904). The reality is that the nurturing programmes are not enhancing membership retention, which points to a disconnect between church offerings and people’s expectations. The findings revealed that 82.4% of the Pastors indicated that the execution initiatives are resulting in low membership retention compared to 78.3% who opined otherwise. Furthermore, with the result showing that there is no statistical association between the execution initiatives and membership retention (χ2(df=1) = 0.102, P = 0.749), this suggests that the aforementioned initiatives are not catering to people’s deeper emotions of belonging and as such accounts for the ineffectiveness of the execution initiatives to retain members in the church. It was found that there was a revealed significant statistical relationship between the two variables (χ2 (df =4) = 28.103, P< 0.0001). It was recommended that Union and local fields should design and implement a Pastors’ training programme to address discipleship, friendly human relations, stewardship, leader and member motivation, conflict resolution, programme design and development and strategic planning to strengthen the structure of the church’s offerings and the faith of members for improved retention.